2009
DOI: 10.2147/ce.s6005
|View full text |Cite
|
Sign up to set email alerts
|

Agomelatine: The evidence for its place in the treatment of depression

Abstract: Introduction: Depressive disorders are among the main causes of disability due to disease. In spite of recent progress in the pharmacotherapy of depression, there is still a high nonresponse rate of ∼30% to the first antidepressant treatment. Furthermore, the latency of several weeks until sufficient clinical improvement and the risk of side effects remain unresolved problems. Therefore, there is still further need for the development of new antidepressants. In the last years a variety of melatonin receptor ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…[13] In addition to those using sepsis models, other studies have demonstrated beneficial effects of melatonin on renal damage as ischemia-reperfusion injury or acute renal failure. [11,18,36] Agomelatine has generally been studied in relation to depressive and anxiety disorders, and, to the best of our knowledge, the present study is the first to research its effects on sepsis-related AKI. Agomelatine has effects similar to those of melatonin, due to its melatonergic receptors.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[13] In addition to those using sepsis models, other studies have demonstrated beneficial effects of melatonin on renal damage as ischemia-reperfusion injury or acute renal failure. [11,18,36] Agomelatine has generally been studied in relation to depressive and anxiety disorders, and, to the best of our knowledge, the present study is the first to research its effects on sepsis-related AKI. Agomelatine has effects similar to those of melatonin, due to its melatonergic receptors.…”
Section: Discussionmentioning
confidence: 87%
“…[8] It is a synthetic drug, an agonist of melatonin receptors (MT1 and MT2) and an antagonist of serotonin receptor (5-HT2C). [9][10][11] Oxidative stress, which plays a key role in pathogenesis of sepsis, is a leading cause of organ dysfunction in particular. [12] Melatonin at high doses is known for its strong antioxidant and anti-inflammatory activity.…”
mentioning
confidence: 99%
“…Superiority was reported over several other drugs both as an antidepressant and in restoring sleep Guilleminault, 2005;Ivanov and Samushiya, 2014;Kasper et al, 2013;Kennedy and Eisfeld, 2007;Martinotti et al, 2012;Owen, 2009). However, the findings have been multiply reviewed, with variable judgments (Anonymous, 2013; Bourin and Prica, 2009;Demyttenaere, 2011;Dolder et al, 2008;Eser et al, 2009Eser et al, , 2007Goodwin, 2009;Guaiana et al, 2013;Howland, 2011aHowland, , 2011bKaminski-Hartenthaler et al, 2015;Kennedy, 2009;Koesters et al, 2013;Langan et al, 2011;MacIsaac et al, 2014;Pandi-Perumal et al, 2008;Singh et al, 2012;Taylor et al, 2014). While positive opinions prevailed especially in the earlier publications, an increasing number of critical or negative conclusions were present later, especially in the larger meta-analyses.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Agomelatine represents the first melatonergic agonist (MT 1 and MT 2 receptors) and 5-HT 2C antagonist [11,12] antidepressant and received a marketing authorization by the European Medicines Agency in 2009. A recently published review aiming to evaluate the safety and efficacy of agomelatine for the treatment of depression, showed that agomelatine was safe and its overall tolerability profile was superior to selective serotonin reuptake inhibitors (SSRIs) or selective serotonin and norepinephrine reuptake inhibitors (SNRIs) [12].…”
Section: Introductionmentioning
confidence: 99%
“…A recently published review aiming to evaluate the safety and efficacy of agomelatine for the treatment of depression, showed that agomelatine was safe and its overall tolerability profile was superior to selective serotonin reuptake inhibitors (SSRIs) or selective serotonin and norepinephrine reuptake inhibitors (SNRIs) [12]. Moreover, a meta-analysis aiming to evaluate the efficacy of agomelatine in MDD revealed that agomelatine was superior to placebo and a number of selected anti-depressants [13].…”
Section: Introductionmentioning
confidence: 99%